Feeding Zinc-Biofortified Wheat Improves Performance, Nutrient Digestibility, and Concentrations of Blood and Tissue Minerals in Quails - Şahin, Nurhan; Küçük, Ömersman; Orhan, Cemal; Savasli, Erdinc; Cakmak, Ismail; Şahin, Kazım (Springernature, 2022)
The present study aimed to investigate the effects of feeding zinc (Zn)-biofortified wheat on performance, digestibility, and concentrations of minerals in quails. Zinc biofortification of wheat has been realized in the field by ergonomically applying Zn to foliar two and three times, which increased grain Zn from 18 mg/kg (control) to 34 and 64 mg/kg. A total of 180 quails were divided into six groups, each containing 30 birds, and fed diets containing wheat grain with either 18, 34, or 64 mg/kg with or without zinc picolinate (ZnPic) supplementation. Bodyweight, feed intake, feed efficiency, and cold carcass weights were greater (P = 0.0001) when the quails were fed a diet containing the biofortified wheat-containing 64 mg Zn/kg. Nitrogen, ash, Ca, P, Zn, Cu, and Fe retentions were greater with the Zn-biofortified wheat-containing 64 mg Zn/kg (P <= 0.026). The nutrient excretions were low with feeding a diet containing biofortified wheat-containing 64 mg Zn/kg (P <= 0.023). Serum, liver, and heart Zn concentrations increased with feeding biofortified wheat-containing 64 mg Zn/kg (P <= 0.002). Thigh meat Fe concentrations increased with increasing Zn concentrations of the wheat samples used (P = 0.0001), whereas the liver Cu concentrations decreased with feeding the wheat-containing 64 mg Zn/kg (P = 0.004). The Zn-biofortified wheat-containing greater Zn concentrations, particularly 64 mg Zn/kg, is a good replacement for corn in the poultry diet as long as its availability and low cost for better performance, greater digestibility, and elevated tissue Zn and Fe concentrations.
Keywords: Zn-biofortified wheat; Zinc picolinate; Performance; Digestibility; Quail